Assessment of impacts on tropical marine environment for off-shore clean energy development. (2020) - Kandlakunta, Laxminarsimha Chary; Deshmukh, M.K.; Sharma, Nitin
Abstract: Off-shore Floating Solar Photovoltaic and Wind Power installations are two potential future clean energy technology options which are being considered by energy developers. Environmental impacts must be evaluated on project-by-project basis as these are site-specific. In the present work, we propose a method for determining baseline reference level of underwater ambient noise in tropical marine coastal shallow waters. The underwater ambient noise has been measured at 30 m depth at a site near Grande island (15°18′ N 73° 41′ E) 18 km off Goa, on India's western coast during 2012–2016. Analysis of recorded data shows that the noise levels in general have increased by a margin of 10–24 dB over the observed frequency band of 10 Hz to 100 kHz, at the site. Therefore, the impacts of clean energy development projects on marine environment need to be evaluated carefully.